Self Tuning of Cascade PI Controller for Buck Converter Based on Adaptive Interaction - Anwari, Sabat (ReTII, 2017)
DCâ€“DC converter convert DC voltage signal from high level to low level signal or it can be vise versa depending on the type of converter used in system. Buck converter is one of the most important components of circuit, it converts voltage signal from high DC signal to low voltage. In buck converter, a high speed switching devices are placed and the better efficiency of power conversion with the steady state can be achieved. Its nonlinearities and uncertainties have increased the complexity of associated controllers so desired performance is achieved. However, cascade-PI controllers are still used to address this problem due to its relative implementation easiness, negating the complexity to the tuning strategy. The relative simplicity of system-specific PI control tuning methods enable a desired system response characteristic: robust, rapid error attenuation with minimal overshoot, zero steady-state off-set, to be easily attained. In this paper, an adaptive interaction is adopted to tune PI controller. The method is simple and effective way to perform gradient descent in the parameter space. The tuning algorithm requires no knowledge of the plant to be controlled. This makes the algorithm robust to changes in the plant. Â Keywords : buck converter, cascade, PI controller, self tuning, adaptive interaction.